Implementation of Spiritual Values in Human Resources Management at the RSCJ Congregation for Nuns - Sidabungke, Henni; Kurniady, Dedy Achmad; Komariah, Aan (Graduate School of Universitas Negeri Malang, 2023)
This research investigates the integration of spiritual values into human resource management (HRM) practices within the RSCJ Congregation for Nuns. The study aims to explore how these values influence the well-being and professional development of nuns. Employing a qualitative approach, the research utilizes a systematic literature review method to analyze secondary data from reputable national and international academic articles. Data collection involved a systematic process, including defining the research question, establishing inclusion and exclusion criteria, searching relevant databases, screening articles, and extracting data. The literature included in the review was selected based on relevance to the research objectives and its ability to address the identified research problem. Data analysis followed interactive model, encompassing data collection, data reduction, data display, conclusion drawing, and verification. The findings indicate that integrating spiritual values into HRM practices promotes a supportive and ethically driven environment, enhancing job satisfaction, organizational engagement, and overall well-being of the nuns. Spiritual leadership emerged as a critical factor in fostering a sense of purpose and belonging, contributing to personal and communal growth. The study's implications extend beyond religious organizations, suggesting that incorporating spiritual values into HRM practices can benefit secular organizations by promoting ethical behavior, enhancing employee well-being, and creating a meaningful work environment. The research highlights the importance of aligning HRM practices with organizational values to support holistic development.